Determination of sin2θw eff using jet charge measurements in hadronic Z decays - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1996)
The electroweak mixing angle is determined with high precision from measurements of the mean difference between forward and backward hemisphere charges in hadronic decays of the Z. A data sample of 2.5 million hadronic Z decays recorded over the period 1990 to 1994 in the ALEPH detector at LEP is used. The mean charge separation between event hemispheres containing the original quark and antiquark is measured forbb¯bb¯ andcc¯cc¯ events in subsamples selected by their long lifetimes or using fastD*’s. The corresponding average charge separation for light quarks is measured in an inclusive sample from the anticorrelation between charges of opposite hemispheres and agrees with predictions of hadronisation models with a precision of 2%. It is shown that differences between light quark charge separations and the measured average can be determined using hadronisation models, with systematic uncertainties constrained by measurements of inclusive production of kaons, protons andΛ’s. The separations are used to measure the electroweak mixing angle precisely as sin2 ϑ effw=0.2322±0.0008(exp.stat.) ±0.0007(exp.syst.)±0.0008(sep.). The first two errors are due to purely experimental sources whereas the third stems from uncertainties in the quark charge separations.